2013
DOI: 10.4236/fns.2013.47090
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Death in Under-Five Children with Sepsis Attending an Urban Diarrheal Treatment Centre in Bangladesh

Abstract: In the logistic regression analysis, after adjusting for potential confounders, such as abnormal WBC count, use of intravenous fluid, patient with fatal outcome more often presented with hypernatremia (odds ratio = 16.48, 95% confidence interval = 2.21 -123.12; p = 0.006), lobar consolidation (odds ratio = 19.9, 95% confidence interval = 2.99 -132.80; p = 0.002), hypoxemia (odds ratio = 14.78, 95% confidence interval = 1.38 -157.90; p = 0.026) and severe under-nutrition (odds ratio = 7.57, 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Sepsis is a clinical syndrome resulting from a dysregulated systemic inflammatory response to infection and characterized by a generalized pro-inflammatory cascade, which may lead to widespread tissue injury [ 24 ]. So, often it leads to severe sepsis, septic shock and multi-organ failure [ 25 ] where the death rate is very high in both developed and developing countries [ 26 , 27 ]. The mortalities vary from 4–34% in sepsis to septic shock [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is a clinical syndrome resulting from a dysregulated systemic inflammatory response to infection and characterized by a generalized pro-inflammatory cascade, which may lead to widespread tissue injury [ 24 ]. So, often it leads to severe sepsis, septic shock and multi-organ failure [ 25 ] where the death rate is very high in both developed and developing countries [ 26 , 27 ]. The mortalities vary from 4–34% in sepsis to septic shock [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortalities vary from 4–34% in sepsis to septic shock [ 28 30 ]. An earlier study in Bangladesh showed the mortality was about 15% in this age group (under five) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of blood isolates was performed following standard microbiological laboratory procedure in the Dhaka Hospital, icddr,b [33].…”
Section: Methodsmentioning
confidence: 99%
“…The identification of blood isolates and the susceptibility testing were done with the routine methods at the microbiological laboratory. Blood culture and serum electrolyte were processed in the Dhaka Hospital, icddr, b [ 20 ].…”
Section: Methodsmentioning
confidence: 99%